Evaluasi Pemanfaatan Aplikasi Pusaka dalam Transformasi Layanan Digital - Muhdi, Muhdi; Jatriyono, Jatriyono; Fikri, M. Haikal; Daeli, Hans Fanolo Kristian (Journal of Electrical Power Control and Automation (JEPCA), 2025)
This study aims to evaluate the implementation success of the Pusaka application, which was developed by the Ministry of Religious Affairs of Indonesia. This application is part of a digital transformation initiative that provides public access to religious services such as hajj registration, marriage, and religious education. The DeLone and McLean Information System Success Model is used as the foundational framework to measure system quality, information quality, use, and user satisfaction. This research tests and validates a pre-formulated model and its hypotheses. The testing is based on primary data collected through an online survey administered to State Civil Apparatus (ASN) within the Muaro Jambi Regency's Ministry of Religious Affairs Office. From the distributed questionnaires, a total of 349 responses were declared valid and suitable for further analysis. The quantitative data in this study were analyzed using the Partial Least Square (PLS) method with the aid of SmartPLS V3 software. The analysis stages included testing the measurement model and the structural model. Based on the data analysis, the results indicate the role of the Pusaka application's utilization in supporting the digital transformation of public services at the Ministry of Religious Affairs.